Study on batch adsorption process of Monoethanolamine (MEA) wastewater treatment using rice husk and banana peels - Mohd Ehran, Razali (2013)
An experimental study was performed in treating Monoethanolamine (MEA) wastewater using bananas peels and rice husk. The main objective of this research is to study the potential of adsorbent usage in treating Monoethanolamine (MEA) wastewater treatment using bananas peels and rick husks. In order to attain maximum result of MEA wastewater treatment, batch process analyses were being done completely. Two important parameters were selected which affected the removal rate of wastewater which are mixing times and adsorbents dosage. From the equipment, it showed that the best potential of adsorbent showed rice husk was better than bananas peels with term percentage of residue oil and reduction of chemical oxygen demand (COD). At 5 wt% (maximum dosage), rice husk removed 43.47% while banana peels removed 41.48% of residue oil of the MEA wastewater. For COD reduction, rice husk manage to reduce 53.32%, while banana peels manage to reduce 49.86% only. At the highest mixing times in 50 minutes, rice husk achieved the highest percentage of oil removal at 78.9% while 76.65% of banana peels. Furthermore, the highest reduction of COD with 52.57% for banana peel and 61.92% reduction for rice husk. Besides, in term of MEA concentration, both adsorbent was not affected by the addition of adsorbent in the MEA wastewater in range below 6% of amine reduction.